The Peptide Methionine Sulfoxide Reductase (MsrAB) of Haemophilus influenzae Repairs Oxidatively Damaged Outer Membrane and Periplasmic Proteins Involved in Nutrient Acquisition and Virulence - Marufa Nasreen; Remya Purushothaman Nair; Alastair G. McEwan; Ulrike Kappler (MDPI AG, 2022)
Sulfoxide-damage repair mechanisms are emerging as essential for the virulence of bacterial pathogens, and in the human respiratory pathogen Haemophilus influenzae the periplasmic MsrAB peptide methionine sulfoxide reductase is necessary for resistance to reactive chlorine species such as hypochlorite. Additionally, this enzyme has a role in modulating the host immune response to infection. Here, we have analysed the enzymatic properties of MsrAB, which revealed that both domains of the protein are catalytically active, with the turnover number of the MsrA domain being 50% greater than that for the MsrB domain. MsrAB was active with small molecular sulfoxides as well as oxidised calmodulin, and maximal activity was observed at 30°C, a temperature close to that found in the natural niche of H. influenzae, the nasopharynx. Analyses of differential methionine oxidation identified 29 outer membrane and periplasmic proteins that are likely substrates for MsrAB. These included the LldD lactate dehydrogenase and the lipoprotein eP4 that is involved in NAD and hemin metabolism in H. influenzae. Subsequent experiments showed that H. influenzae MsrAB can repair oxidative damage to methionines in purified eP4 with up to 100% efficiency. Our work links MsrAB to the maintenance of different adhesins and essential metabolic processes in the H. influenzae, such as NAD metabolism and access to L-lactate, which is a key growth substrate for H. influenzae during infection.